FAKTOR-FAKTOR YANG MEMENGARUHI STRUKTUR MODAL PERUSAHAAN SEKTOR KONSUMEN NON-CYCLICAL DI BURSA EFEK INDONESIA PERIODE 2019-2021 - Elora, Elora; Sufiyati, Sufiyati (Jurnal Paradigma Akuntansi, 2025)
This study aims to obtain empirical evidence regarding the effect of sales growth, asset structure, company size, profitability, and liquidity on the capital structure of non-cyclical consumer sector companies on the Indonesia Stock Exchange for the 2019-2021 period. The sample was selected by purposive sampling method and valid data were 132 data from 44 companies. The research data were processed using statistical software Eviews 12 Student Version to perform multiple linear regression analysis, classical assumption test, and hypothesis test. The results shown in this study are that asset structure and liquidity have a negative effect on capital structure. While sales growth, company size and liquidity have no effect on capital structure. The implication of this research is to become a reference for managers to consider and pay attention to the factors that affect the company's capital structure. Then, it provides a reference for investors in considering their decision to invest and also serves as a scientific reference and provides the latest information regarding capital structure.